Conducted emission study in space vector modulated voltage source inverter - Uma Maheswari Yuvaraj; Amudha Alagarsamy; Ashok Kumar Loganathan; Selvathai Thavassy (Institute of Advanced Engineering and Science, 2022)
To comply with electromagnetic interference (EMI) standards, the electromagnetic noise generated by power electronic converters must be analyzed and suppressed since the switching frequency of the converter affects EMI noise. Conducted emission occurs in drive systems due to inverter parasitic capacitances and rapidly switching inverter output voltages. The EMI noise produced space vector pulse width modulation (SVPWM) inverter is calculated using MATLAB/Simulink simulation data. The unwanted common mode and differential mode signals produced by the inverter are captured using a spectrum analyzer and examined using short time Fourier transform (STFT). To mitigate the effect of EMI in the circuit and to comply with the standards filters are developed. The passive filter components are defined by the EMI standards attenuation requirements. The MATLAB simulation findings are confirmed and verified by hardware implementation.